HEALTH INSURANCE IN CHINA AND THE POSSIBILITIES OF INTEGRATING ITS ELEMENTS INTO THE HEALTHCARE SYSTEM OF UZBEKISTAN - Mamadaliyeva Umida Pulatovna; Toshxojaeva Dilbar Saidaxmad qizi (Web of Journals Publishing, 2025)
The thesis examines the characteristics, organizational structure, financing sources, and coverage level of the health insurance system of the People’s Republic of China. It analyzes China’s experience in reforming its compulsory health insurance system. Special attention is given to the potential adaptation of certain elements of the Chinese model within the context of Uzbekistan, particularly regarding the digitalization of insurance services, the implementation of a family doctor system, and the development of national mechanisms for quality control of medical care.
Keywords: Health insurance, China, Uzbekistan, compulsory health insurance, healthcare system, digitalization of medical services, DMED, Chinese experience, family doctors, medical care quality control, financing sources, insurance coverage, international insurance, healthcare reforms, multi-level insurance system.